Intramatricial platelet‐rich plasma therapy: A novel treatment modality in refractory nail disorders. Issue 2 (18th February 2019) - Kaur, Ishmeet; Jakhar, Deepak
Abstract: Two patients, one with nail lichen striatus and second with idiopathic trachyonychia were treated with intramatriceal injections of platelet‐rich plasma. A total of 0.1 ml of the plasma solution was injected into the matrix of the involved nails at three weekly intervals. Follow‐up was done at each sitting and thereafter at 16 and 20 weeks. Assessment was done both photographically and by dermoscopy. Case 1 showed marked improvement within 3 weeks and Case 2 showed improvement within 6 weeks. No relapses were seen at 16 and 20 weeks of follow up. Intramatricial PRP is a safe and effective therapeutic modality in nail lichen striatus and idiopathic trachyonychia refractory to other treatment options. Further studies with larger sample size and controls are required to validate the results.